Sago Wastewater : Characterization and Degradation by TiO2 photocatalysis - Devagi, Kanakaraju; Pang, Wong Soon; Muhammad Mashur, Bear (Department of Wildlife and National Parks, 2023)
One of the major sectors which have been contributing to the deterioration of water resources as well as accumulation of solid wastes is agriculture. One of the most important crops for starch production is sago palm. It is known that more than 90% of sago-planting areas are found in the state of Sarawak, Malaysia. Heavy consumption of water by sago starch production mills have resulted in large volumes of sago effluent. Direct release of sago wastewater into water bodies may be inappropriate due to the high amount of organic material, and suspended solids. There are also growing concerns about the solid wastes which include sago roughage (hampas), and sago bark. Hence, an effective method or protocol becomes necessary to tackle issues related to this agro industry. Titanium dioxide (TiO2) photocatalysis is known for its potential to effectively treat various types of wastewater. However, there remains a paucity of studies on sago wastewater abatement over TiO2 photocatalysis. The objective of this study is to investigate the potential of TiO2 photocatalysis for the degradation of sago wastewater. Discussion pertaining to the properties of sago wastewater and solid residues, performance of TiO2 photocatalysis and recommendation for future studies are outlined.